Factors that influence Malaysian-based financial literacy model among teenagers - Khoo Yin Yin; Rohaila Yusof; Wei Chooi Yi (International Journal of Evaluation and Research in Education (IJERE), 2022)
Most of the young generation do not realize the importance of decision making, money-saving, and budget planning. Consequently, a total of 47% of bankruptcies in Malaysia occurred among young adults between the ages of 18-35. Young individuals account for the majority of bankruptcies, public awareness of financial literacy should be raised. More effective teaching in secondary school has attracted researchers' attention. One of the general objectives of the Malaysian curriculum for the students is to practice moral values. Money-saving can be considered as one of the moral values. Still, school teachers have to cover many other academic topics, and they always feel overburdened with all types of examination-oriented textbooks. Students' value towards money and attitude influence their financial decision. Other factors needed in financial literacy are decision-making and accountability. This study aimed to examine factors that influence students' human values in financial literacy. This study had instilled human values to encourage students to practice time-saving, decision making, money-saving, and other values related to their well-being in the future. The survey was employed in this study. Then, a video that integrated financial literacy and human values with a Malaysian-based real-world learning experience was created in stage two. In addition, the questionnaire was administered to 327 secondary school students after they watched the video. The structural equation modeling method was used to determine the factors that influenced the financial literacy model. The findings from the analysis retained four elements: practices, decision making, accountability, and human values. Future research can focus on a comparative analysis with neighboring countries.